Convective Vortices and Dust Devils Detected and Characterized by Mars 2020. Issue 2 (10th February 2023) - Hueso, R.; Newman, C. E.; del Río‐Gaztelurrutia, T.; Munguira, A.; Sánchez‐Lavega, A.; Toledo, D.; Apéstigue, V.; Arruego, I.; Vicente‐Retortillo, A.; Martínez, G.; Lemmon, M.; Lorenz, R.; et al.
Abstract: We characterize vortex and dust devils (DDs) at Jezero from pressure and winds obtained with the Mars Environmental Dynamics Analyzer (MEDA) instrument on Mars 2020 over 415 Martian days (sols) ( Ls  = 6°–213°). Vortices are abundant (4.9 per sol with pressure drops >0.5 Pa correcting from gaps in coverage) and they peak at noon. At least one in every five vortices carries dust, and 75% of all vortices with Δ p > 2.0 Pa are dusty. Seasonal variability was small but DDs were abundant during a dust storm ( Ls  = 152°–156°). Vortices are more frequent and intense over terrains with lower thermal inertia favoring high daytime surface‐to‐air temperature gradients. We fit measurements of winds and pressure during DD encounters to models of vortices. We obtain vortex diameters that range from 5 to 135 m with a mean of 20 m, and from the frequency of close encounters we estimate a DD activity of 2.0–3.0 DDs km −2 sol −1 . A comparison of MEDA observations with a Large Eddy Simulation of Jezero at Ls  = 45° produces a similar result. Three 100‐m size DDs passed within 30 m of the rover from what we estimate that the activity of DDs with diameters >100 m is 0.1 DDs km −2 sol −1, implying that dust lifting is dominated by the largest vortices in Jezero. At least one vortex had a central pressure drop of 9.0 Pa and internal winds of 25 ms −1 . The MEDA wind sensors were partially damaged during two DD encounters whose characteristics we elaborate in detail. Plain Language Summary: Dust devils (DDs) are whirlwinds of warm air with winds strong enough to lift dust. They are common in Earth deserts and much more abundant on Mars, where they are one of the elements that bring dust to the atmosphere. The Mars 2020 mission landed in Jezero crater on February 2020 and has observed a plethora of DDs that we investigate with the meteorological sensors on the Mars Environmental Dynamics Analyzer (MEDA) instrument. Results for more than 400 Martian days from spring to autumn indicate a high abundance of events with small seasonal variability. Terrains with lower thermal inertia, warming more efficiently at noon, favor the appearance of DDs. We also found an increased DD activity during a short dust storm that covered the region. From modeling MEDA data, we find that DDs at Jezero have diameters from 5.0 to 135 m. We estimate that about 2–3 DDs are formed per km 2 and Martian day. Large vortices with diameters of 100 m form frequently enough to dominate dust lifting at Jezero. Two DDs damaged part of the hardware of the wind sensors of MEDA and we detail the characteristics of those events. Key Points: Vortices and dust devils (DDs) are frequent on Jezero. Mars Environmental Dynamics Analyzer detects 5.0 and 1.0 events per sol respectively when correcting from sampling effects Intense vortices on Jezero tend to be dusty with 75% of all vortices with a pressure drop larger than 2.0 Pa being dusty We calculate 2.5 and 0.1 DDs km −2 sol −1 with sizes of 20 and 100 m respectively. The largest events dominate dust lifting